AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT - Cipta, Berry Santrio; Husnayaini, Ihda; Rasuan, Zulfikri B (EEdJ: English Education Journal, 2021)
This research is aimed to find out the ability and difficulties of public school students in Jebus, Bangka in writing descriptive text. The method used in this research is descriptive quantitative. The researcher used writing test as the instrument. The sample of this research was the second grade of a public school in Jebus which consists of 30 students selected by using purposive sampling. The finding indicated that the students’ ability in writing descriptive text was classified into very poor. The students’ writing ability in content categories was 2,63, in organization was 2,09, in vocabulary was 2,93, in grammar was 1,75. And in mechanic was 2,33. They were all classified very poor. While the students’ difficulties in writing was language features of descriptive text which consist of describing object in detail, lack of vocabulary and grammar mastery. Therefore, the majority of students was found it difficult to write correct spelling words and create sentences. Based on the results, the researcher concluded that the students did not have good understanding and ability in writing descriptive text.